Effect of systemic administration of omeprazole on osseointegration around titanium dental implants: A histomorphometric study in dogs - Negar Kanounisabet; Ahmad Mogharehabed; Nakisa Torabinia; Seyedeh Marzieh Hashemi Nejad; Jaber Yaghini (Wolters Kluwer Medknow Publications, 2021)
Background: Dental implants are widely accepted substitutes for replacing missing teeth. Many factors, including the use of specific drugs such as proton-pump inhibitors (PPIs) (omeprazole), can affect the success of dental implantations. The aim of this study was to investigate the relationship between the use of omeprazole and osseointegration of dental implants. Materials and Methods: This experimental animal study was performed on eight native male dogs weighted 11-13 kg and aged 16-20 months. The dogs were divided into two groups (receivers and nonreceivers of omeprazole). After extraction of mandibular teeth, treatment was started randomly with the administration of omeprazole and saline. After a 2-month recovery period, six titanium implants were placed in the jaws of all dogs and the administration of omeprazole was continued for 2 weeks. After 4 and 12 weeks, the dogs were anesthetized and dental implants with their bone marrow were removed. The samples were examined histomorphometrically to determine osseointegration. Data were analyzed with two-way ANOVA test for 95% confidence interval. The P value was set at 0.05. Results: In the microscopic examination of the samples in week 4, the levels of bone-implant contact (BIC) in the study group were significantly lower than the control group (46.37 vs. 64.37%). In 12 weeks, BIC was significantly lower than that of the control group (67.33 vs. 82.00%). The type of bone formed in week 4 in both the groups was more woven, and in the 12th week, it was mostly lamellar. Conclusion: Systemic administration of PPIs may interfere with osseointegration of dental implants.